2019
DOI: 10.1371/journal.pone.0219298
|View full text |Cite
|
Sign up to set email alerts
|

How does emotion influence the creativity evaluation of exogenous alternative ideas?

Abstract: The interaction of emotions with creative cognition is one of the most intriguing topics in the creativity research. In this study, we investigated the extent to which various emotional states influence the evaluation of ideas, which is a crucial component of the creative thinking process. To this end, we used emotional (both positive and negative) and neutral pictures to induce emotional states and then asked participants to evaluate the creativity of exogenous ideas (i.e., those generated by other people) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 80 publications
3
24
1
Order By: Relevance
“…These findings are consistent with the results of past research showing the incremental effect of positive emotions over creative performance (Ashby et al, 1999;Forgas, 2000;Isen et al, 1987). Whereas past creativity research induced positive states using different experimental manipulations (Baas et al, 2008;Mastria et al, 2019), in the present study the manipulation was induced through the exposure to specifically designed VEs. The emotional reactions emerging during the exposure to VEs should be therefore taken into consideration as one of the possible mechanisms explaining the influence of virtual reality on the creative behavior.…”
Section: Creative Performance and Opennesssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with the results of past research showing the incremental effect of positive emotions over creative performance (Ashby et al, 1999;Forgas, 2000;Isen et al, 1987). Whereas past creativity research induced positive states using different experimental manipulations (Baas et al, 2008;Mastria et al, 2019), in the present study the manipulation was induced through the exposure to specifically designed VEs. The emotional reactions emerging during the exposure to VEs should be therefore taken into consideration as one of the possible mechanisms explaining the influence of virtual reality on the creative behavior.…”
Section: Creative Performance and Opennesssupporting
confidence: 92%
“…A further interesting result emerging from the current study showed that the Openness personality trait is able to influence participants' creative performance also in VEs. Openness has been indeed showed to be one of the most influential variables affective creative behavior (Corazza & Agnoli, 2019;Feist, 1998). Even if its effect emerged as consistent in all the tested environments, our results revealed that Openness was more effective in increasing response originality in the PVE in comparison to the other environments.…”
Section: Creative Performance and Opennesscontrasting
confidence: 51%
“…The effect of mood on creative ideation (more solutions) is higher in positive affect and creative evaluation (more accuracy) is higher on negative affect. Past research also reveals that idea-evaluation process can be created with an affective arousing situations, thus effect people's evaluation of creativity with those emotions (Mastria et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fluency, originality, flexibility, and elaboration act as supportive roles in accelerating the creative thinking cognition process (Runco and Acar, 2012). The interactive role of emotions in the creative thinking process is one of the most intriguing research topics on creative thinking (Baas et al, 2008;Ding et al, 2015;Mastria et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the existence of a close relationship between emotions and creative thinking has been reported widely, there is no clear consensus on how these connections exist in the cognitive process. Studies have reported that individuals with positive emotions activated positive information connections and cognitive flexibility to enhance the fluency, originality, and insight; but individuals' negative emotions had negative impact on the creative thinking process (Isen et al, 1986;Fernández-Abascal and Díaz, 2013;Mastria et al, 2019). However, some studies supported that negative emotions can stimulate an individual's exploration of the real environment to improve the creative thinking process (Damian and Robins, 2012;Eastwood et al, 2012;Van Tilburg and Igou, 2012).…”
Section: Introductionmentioning
confidence: 99%